2016
DOI: 10.1007/s40808-016-0200-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of satellite based rainfall products on river basin responses of runoff simulation on flood event

Abstract: Physically-based distributed hydrological modelling, Rainfall-Runoff-Inundation (RRI) model is used to evaluate runoff accuracy by using six satellite based rainfall products such as GPM, GSMaP, TRMM 3B42V7, CMORPH, and PERSIANN. These products input to drive the model on the Nan River basin, Thailand that is the watershed of 13,000 km 2 . The performance of the precipitation products, rainfall depth and runoff, was evaluated from storm event on 2014 by using statistical approach, Volume bias, Peak bias, RMSE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
(40 reference statements)
0
27
0
Order By: Relevance
“…We found that daily IMERG V5 has the highest accuracy; this is consistent with the evaluation studies [17,19], which show that IMERG estimations exhibit notable improvements over TRMM to detect heavy storms and precipitation at sub-daily and daily resolution. A study in the Nan river basin of Thailand [39] revealed that mean bias of TRMM and GPM was about +4.5 mm/day and +1.54 mm/day, respectively. Our study reveals higher accuracies of TRMM and GPM products in northeastern Thailand.…”
Section: The Comparison Of Precipitation Productsmentioning
confidence: 99%
“…We found that daily IMERG V5 has the highest accuracy; this is consistent with the evaluation studies [17,19], which show that IMERG estimations exhibit notable improvements over TRMM to detect heavy storms and precipitation at sub-daily and daily resolution. A study in the Nan river basin of Thailand [39] revealed that mean bias of TRMM and GPM was about +4.5 mm/day and +1.54 mm/day, respectively. Our study reveals higher accuracies of TRMM and GPM products in northeastern Thailand.…”
Section: The Comparison Of Precipitation Productsmentioning
confidence: 99%
“…The V4 IMERG data prior to March 2014 will also be processed retrospectively in late 2017. To date, researchers have identified both the uncertainty and error characteristics of the V3 IMERG datasets [34][35][36][37][38][39][40][41]. At present, a quantitative evaluation of the similarities and differences between the successive V3 and V4 products and of the global improvements of V4 over V3 are urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…Such satisfying results had also reported in [31,33]. It is unanticipated, in particular, the GSMaP-NRT data, as studies found that GSMaP had a significant discrepancy with observed data in rainfall estimation [68][69][70] and runoff simulation [71]. In Malaysia, rainfall estimates using SRPs have been carried out in several studies [19,20,72].…”
Section: Resultsmentioning
confidence: 60%